Epic vs. Buddhist Literature: the case of Vidhurapaṇ ḍ itajā taka - Gönc Moačanin, Klara (Array, 2009)
Klara Gönc Moačanin also explores the relationship between the Mahā bhā rata and the Buddhist tradition in the traces of Lüders, and concentrates on the parallel between the Vidhurapaṇ ḑ itajā taka and the dice game episode in the Sabhā parvan. The correspondences include the situation – the game of dice, the protagonists - Vidhura vs. Vidura, Dhanañ ; jaya vs. Arjuna Dhanaṃ jaya, the place of the capital – Indapatta vs. Indraprastha. The differences are striking – Dhanañ ; jaya is king, not Yudhiṣ ṭ hira, the game is not about the division of the kingdom, but the stake in the game is the minister Vidhura, the motive is not the wish to rule the kingdom, but the wish of the wife of the Nā ga king to hear words of wisdom from Vidhura, and the general Puṇ ṇ aka's love for the king's daughter. Gönc Moačanin stresses that the core of the Jā taka must be the gā thā s, accepts Alsdorf's claim that a half of them (ca. 150) could be genuine, perceives the Jā taka story as a yakkha / yakṣ a tale in contradistinction to the epic as a part of the Great Tradition, and suggests that both stories, the Buddhist and the epic one, must have originated from the „ floating literature“ (an older term for non-recorded oral tradition) which must have undergone Buddhist, epic and narrative stylizations in the works that have come down to us. In that process each of the three traditions must have used the elements from that common source for its own purposes.